On the mechanism of loading the PCNA sliding clamp by RFC. - Dionne, I; Brown, N; Woodgate, R; Bell, S (2008)
Sliding clamps play central roles in a broad range of DNA replication and repair processes. The clamps form circular molecules that must be opened and resealed around DNA by the clamp loader complex to fulfil their function. While most eukaryotes and many archea possess a homo-trimeric PCNA, the PCNA of Sulfolobus solfataricus is a heterotrimer. Here, we exploit the asymmetry of S. solfataricus PCNA to create a series of circularly permuted PCNA subunit fusions, thereby covalently closing defined interfaces within the heterotrimer. Using these concatamers, we investigate the requirements for loading the clamp onto DNA and reveal that a single defined interface within the heterotrimer is opened during the loading process. Subunit-specific interactions between S. solfataricus RFC clamp loader and PCNA permit us to superimpose our data upon the structure of yeast RFC-PCNA complex, thereby presenting a general model for PCNA loading by RFC in archaea and eukaryotes.